Fortifying Trust, Security, and Privacy in Online Trading Systems: Unlocking their Paramount Significance - Omkar Poudel,; Pradeep Acharya ,; Daya Simkhada, (Journal of Balkumari College, 2023)
The purpose of the study is to examine the impact of perceived security and perceived privacy on customers trust to accept the use online trading system in an extended form of the tam model with TAM constructs. This research paper tries to study the impact of security and privacy perceptions on customer’s trust, also the impact of perceived usefulness and perceived ease of use on customer’s intention to use online trading system. For the purpose of the study total of 201 samples were collected through the online survey and the data so collected was analyzed descriptively in SPSS version 24, and the seven hypotheses were tested using PLS-SEM in SmartPLS. The path modeling through PLS indicated that perceived ease of use and privacy has no significant positive relation with behavioral intention and trust respectively but all others hypothesis were accepted and the research showed that trust plays an important role for customers intention to use online trading system.